The Effect of Diagnostic Assessment Strategy on Learning Football Shooting Skills Among Students (Journal of the College of Basic Education, 2025)
The research aimed to investigate the impact of the diagnostic evaluation strategy on learning football scoring skills among students at Al-Mahmoudiya Scientific Preparatory School for Boys, affiliated with the Second Al-Karkh Directorate . The researcher hypothesized that there are statistically significant differences between the pre-test and post-test results of the experimental and control groups ، in favor of the post-test . The researcher used the experimental method with pre- and post-tests . The study sample consisted of fifth-grade science students, totaling (62) students ، divided into experimental and control groups . The post-test results between the two groups showed a positive effect on learning football scoring skills. Additionally ، the researcher recommended the importance of leveraging the advantages of the diagnostic evaluation strategy for learning football skills in particular and sports skills in general .